Analysis of highly dangerous and economically important animal disease situation in CIS countries in 2013-2015 - D. A. Lozovoy (Ветеринария сегодня)
The epizootic situation in the CIS Member States for 2013-2015 was characterized on the basis of materials provided by heads of the veterinary services of the CIS Member States to the CIS Executive Committee, on the basis of the OIE data supplemented by information from the Rosselkhoznadzor Information Analysis Centre and taking into account reports from the meetings of the CIS Intergovernmental Council for Veterinary Cooperation for 2013-2016. Their territories remain infected with highly dangerous animal diseases such as rabies, African swine fever, sheep and goat pox, foot-and-mouth disease, anthrax, etc.